Can Tumor Recurrence Be Predicted by Magnetic Resonance Imaging Findings Before Microwave Ablation in Patients with Hepatocellular Carcinoma? - Mustafa Özdemir (Sakarya Tıp Dergisi)
Objective: Hepatocellular carcinoma (HCC) is a common cancer. The primary treatment is surgery or liver transplantation. Percutaneous ablation techniques constitute the primary treatment in patients who are not suitable for surgery. Although it gives successful results, some studies report a recurrence rate of up to 50%. This study aimed to obtain an idea about the possibility of possible recurrence by evaluating the lesion characteristics in the pre-procedural MRI images of patients with and without recurrence. Methods: Forty-eight patients who underwent microwave ablation for HCC in our center between 2018 and 2021 were included in the study. Lesion size, presence of peripheral enhancement, arterial contrast enhancement, and T2 signal characteristics were evaluated on pre-procedural MRI. Subsequently, the relationship of these features with tumor recurrence was evaluated. Results: The risk of recurrence was higher in patients with lesion sizes with larger than 3 cm diameter and in lesions showing peripheral contrast enhancement (p= 0.036 and p= 0.021, respectively). Conclusion: Close follow-up will be beneficial in HCCs larger than 3 cm and showing peripheral enhancement since there is a high probability of recurrence after ablation.